2012
DOI: 10.1007/s10856-012-4662-y
|View full text |Cite
|
Sign up to set email alerts
|

Repair of rabbit femoral condyle bone defects with injectable nanohydroxyapatite/chitosan composites

Abstract: Repair of massive bone loss remains a challenge to the orthopaedic surgeons. Autologous and allogenic bone grafts are choice for bone reconstructive surgery, but limited availability, risks of transmittable diseases and inconsistent clinical performances have prompted the development of tissue engineering. In the present work, the bone regeneration potential of nanohydroxyapatite/chitosan composite scaffolds were compared with pure chitosan scaffolds when implanted into segmental bone defects in rabbits. Criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…Zhang et al 44 developed an injectable nano-HAp/chitosan scaffold for repairing rabbit femoral condyle bone defects with critical size bone defects (6 mm in diameter and 10 mm in length). Twelve weeks after surgery, complete healing of the segmental bone defect was observed in the nano-HAp/chitosan group, whereas the defect was still visible in the chitosan group, although the depth of the defect had diminished.…”
Section: Histological Resultsmentioning
confidence: 99%
“…Zhang et al 44 developed an injectable nano-HAp/chitosan scaffold for repairing rabbit femoral condyle bone defects with critical size bone defects (6 mm in diameter and 10 mm in length). Twelve weeks after surgery, complete healing of the segmental bone defect was observed in the nano-HAp/chitosan group, whereas the defect was still visible in the chitosan group, although the depth of the defect had diminished.…”
Section: Histological Resultsmentioning
confidence: 99%
“…Whitlockite (WH: Ca 18 Mg 2 (HPO 4 ) 2 (PO4) 12 ), a second most abundant mineral in living bone (about 20% based on the amount of Mg substitution of calcium ions with magnesium ions in calcium orthophosphate crystal. [11][12][13] Recently, Jang et al 14 evaluated the bioactive properties of WH nanoparticles through in vitro and in vivo tests and compared the results with those of HAP and β-tricalcium phosphate (β-TCP; β-Ca 3 (PO 4 ) 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan, an ideal biomaterial with excellent biocompatibility and antibacterial capability, has been widely applied in tissue engineering and bone repair. [15][16][17][18][19] Therefore, we chose chitosan as the organic phase to fabricate the inorganic/organic composite porous scaffold for bone regeneration. First, we prepared HAP and WH hollow microspheres by using creatine phosphate (CP) disodium salt as an organic phosphorus source in aqueous solution by microwave-assisted hydrothermal method.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is substitute material for bone defects because of its high biocompatibility, osteoconductivity, antimicrobial, biodegradability and adsorption properties (Zhang et al 2012). Bioactive glass can bond spontaneously to living bones without forming fibrous tissue at the interface (Shi et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2012) suggested that an injectable nanohydroxyapatite/chitosan scaffold was a potential candidate material for regeneration of bone loss. Vestergaard et al (2010) indicated that the use of Ostene instead of bone wax could contribute to a reduction in the incidence of sternal dehiscence and chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%